Personalized Medicine: Challenge and Promise - Kaur, Judith Salmon (2012)
The new health care buzz words include “personalized or individualized medicine.” Populations such as American Indians and Alaska Natives potentially have much to gain from this new science to overcome the known health disparities in these populations. This will require participation and acceptance of diverse populations. This article reviews the promise and challenges of individualizing cancer care using principles of community-based participatory research.